2013
DOI: 10.1002/lsm.22159
|View full text |Cite
|
Sign up to set email alerts
|

High contrast reflectance imaging of simulated lesions on tooth occlusal surfaces at near‐IR wavelengths

Abstract: Introduction In vivo and in vitro studies have shown that high contrast images of tooth demineralization can be acquired in the near-infrared (near-IR) without the interference of stain. The purpose of this study is to compare the lesion contrast in reflectance at near-IR wavelengths coincident with high water absorption with those in the visible, the near-IR at 1,300 nm and with fluorescence measurements for early lesions in occlusal surfaces. Methods Twenty-four human molars were used in this in vitro stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

9
1

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…As a result analysis of images has been based on the increased signal intensity values to quantify parameters such as depth and mineral loss. Unlike the other optical techniques OCT produced images of the microstructure of tooth tissues assessed from the outer surface towers the pulp [17][18][19].…”
Section: Polarization -Sensitive Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…As a result analysis of images has been based on the increased signal intensity values to quantify parameters such as depth and mineral loss. Unlike the other optical techniques OCT produced images of the microstructure of tooth tissues assessed from the outer surface towers the pulp [17][18][19].…”
Section: Polarization -Sensitive Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…Hyperspectral reflectance measurements by Zakian et al show that the tooth appears darker with increasing wavelength. 7 Recent studies by Chung et al 15 and Fried et al 20 on natural and simulated occlusal lesions indicated that other NIR wavelengths coincident with higher water absorption provide significantly higher contrast than at 1300 nm or at visible wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that near-IR reflectance imaging beyond 1200-nm is well-suited for imaging carious lesions without the interference of stains [1, 2]. Conventional visible reflectance and quantitative light fluorescence techniques for carious lesion detection yield low lesion contrast and are plagued with poor sensitivity due to stains masking demineralization [3, 4].…”
Section: Introductionmentioning
confidence: 99%